Analysis of Factors Affecting the Performance of Accounting Information Systems in Village Credit Institutions of Ubud District - Astawa, Dewa Gde Yudhi; Anak Agung Ngurah Agung Kresnandra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The Village Credit Institution (LPD) is one of the financial institutions that utilizes a computer-based accounting information system (SIA). Complete and accurate financial reports are needed to assess the performance of an LPD, therefore the support of AIS with computerized information technology is very necessary. Assessing the performance of an accounting information system (AIS) to shape the success of the development of the system itself is an important issue, so that it can provide added value. The objectives of this study are to empirically test the existence of user involvement, top management support and personal technical skills on the performance of the Accounting Information System at the Village Credit Institution, Ubud District. The method of determining the sample used is purposive sampling. The data collection method in this study is a survey method by distributing questionnaires directly to respondents. Data were analyzed using descriptive statistical analysis techniques, classical assumptions, multiple linear regression. The results of the study indicate that user involvement has a positive and significant effect on the performance of accounting information systems. Top management support has a positive and significant effect on the performance of accounting information systems. Personal technical ability has a positive and significant effect on the performance of accounting information systems. The implications of this research are theoretical implications and practical implications.